Ectopic expression of DnaJ type-I protein homolog of Vigna aconitifolia (VaDJI) confers ABA insensitivity and multiple stress tolerance in transgenic tobacco plants - Gautam, Ranjana; Meena, Rajesh Kumar; Rampuria, Sakshi; Shukla, Pawan; Kirti, P. B. (Frontiers in Plant Science, 2023)
Reduced crop productivity results from altered plant physiological processes caused by dysfunctional proteins due to environmental stressors. In this study, a novel DnaJ Type-I encoding gene, VaDJI having a zinc finger motif in its C-terminal domain was found to be induced early upon treatment with heat stress (within 5 min) in a heat tolerant genotype of Vigna aconitifolia RMO-40. VaDJI is induced by multiple stresses. In tobacco, ectopic expression of VaDJI reduced ABA sensitivity during seed germination and the early stages of seedling growth of transgenic tobacco plants. Concomitantly, it also improved the ability of transgenic tobacco plants to withstand drought stress by modulating the photosynthetic efficiency, with the transgenic plants having higher Fv/Fm ratios and reduced growth inhibition. Additionally, transgenic plants showed a reduced build-up of H2O2 and lower MDA levels and higher chlorophyll content during drought stress, which attenuated cell damage and reduced oxidative damage. An analysis using the qRT-PCR study demonstrated that VaDJI overexpression is associated with the expression of some ROS-detoxification-related genes and stress-marker genes that are often induced during drought stress responses. These findings suggest a hypothesis whereby VaDJI positively influences drought stress tolerance and ABA signalling in transgenic tobacco, and suggests that it is a potential gene for genetic improvement of drought and heat stress tolerance in crop plants.